Penelitian Hukum: Dari Monodisipliner Ke Interdisipliner - RIKARDO SIMARMATA (Fakultas Hukum Universitas Mulawarman, 2008)
More than successfully matching the doctrinal law science and social science, the studies ofsocio-legal keep the distance between both closer. A way to do this seems through suggesting forthe social sciences, like sociology, to avoid from the allergy against studying the doctrine andcontent of law. Law sociology contributes to the explanation of the nature of law through itsempirical studies. Any contributions from the legal ideas actually emanate from the law philosophy.Instead, the doctrinal law science needs to develop the review on law texts using theories orconcepts of social sciences. Such steps become trustable since the legal rules appear away from theprevious simplicity, following the more developed regulatory rules.Key words: penelitian hukum doktrinal (doctrinal legal research), ilmu sosial (social science), penelitianhukum sosial (socio-legal studies).